Vitamins A, and C and folate status in Mexican children under 12 years and women 12-49 years: a probabilistic national survey Estado de las vitaminas A y C, y folato en niños menores de 12 años de edad y mujeres de entre 12 a 49 años de edad: una encuesta probabilística nacional - Salvador Villalpando; Irene Montalvo-Velarde; Norma Zambrano; Armando García-Guerra; Claudia Ivonne Ramírez-Silva; Teresa Shamah-Levy; Juan A Rivera (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To describe the epidemiology of Vitamin A and C and folic acid deficiencies and their association with sociodemographic and dietary factors in a national probabilistic sample of Mexican women and children. MATERIAL AND METHODS: This is a probabilistic sample from the National Nutrition Survey 1999 (ENN-99) including 1 966 children and 920 women. Vitamins A and C were measured in serum by high-performance liquid chromatography, and folic acid in total blood by a microbiological method. Determinants for such deficiencies were explored by multiple regression models. RESULTS: Vitamin A deficiency (retinol <10 µg/dl) was rare in both children and women. But subclinical deficiency (retinol >10 and <20 µg/dl) was present in 25% of children. The likelihood of subclinical deficiency of vitamin A was less in older children (OR=0.98, p=0.01) and in women with higher body mass index (OR=0.93, p=0.01). About 30% of children <2 years of age and 40% of women were vitamin C deficient. The likelihood of vitamin C deficiency was less in children and women as socioeconomic level increased (OR=0.69, p=0.03, and OR=0.80, p=0.04), and higher in older women (OR=1.02, p=0.05). The prevalence of folate deficiency varied in children (2.3 to 11.2), in women it was 5%. Folate deficiency was less in children of higher socioeconomic level (OR=0.62, p=0.01 ), and in those eating more vegetables (OR= 0.22, p=0.01). CONCLUSIONS: The high prevalence of subclinical deficiency of vitamin A in children is indicative of risk of further deterioration under adverse circumstances. Vitamin C deficiency in both children and women implies in addition diminished ability for iron absorption. OBJETIVO: Describir la epidemiología de las deficiencias de las vitaminas A y C y del ácido fólico, y analizar su asociación con factores sociodemográficos y dietéticos en una muestra probabilística nacional de mujeres y niños mexicanos. Informar acerca del estado nutricio de estas vitaminas en una muestra probabilística nacional en México. MATERIAL Y MÉTODOS: Esta muestra probabilística de la Encuesta Nacional de Nutrición 1999 incluyó 1 966 niños y 920 mujeres. Las concentraciones séricas de las vitaminas A y C fueron medidas por cromatografía líquida de alta resolución HPLC (por sus siglas en inglés) y las de ácido fólico en sangre total por un método microbiológico. Se exploraron los posibles determinantes de la deficiencia de tales nutrimentos mediante modelos de regresión logística. RESULTADOS: La deficiencia de vitamina A (retinol <10 µg/dl) fue rara, tanto en niños como en mujeres. El 25% de los niños de 1 a 8 años de edad tuvieron deficiencia subclínica (retinol >10 <20 µg/dl). El riesgo de tener deficiencia subclínica de vitamina A fue menor en los niños de mayor edad (OR=0.98, p=0.01) y en mujeres con mayor índice de masa corporal (OR=0.93, p=0.01). El 30% de los niños <2 años de edad y 40% de las mujeres tuvieron deficiencia de vitamina C. El riesgo de esta deficiencia fue menor en niños y mujeres de nivel socioeconómico alto (OR=0.69, p=0.03, y OR=0.80, p=0.04), y mayor en mujeres de mayor edad (OR=1.02, p=0.05). En los niños la prevalencia de deficiencia de ácido fólico varió entre 2.3 y 11.2%, en las mujeres de 5%. El riesgo de tener deficiencia de folatos fue menor en niños con nivel socioeconómico alto (OR=0.66, p=0.04), y menor en aquellos que consumían más vegetales (OR= 0.22, p=0.01). CONCLUSIONES: La alta prevalencia en México de deficiencia subclínica de vitamina A en niños y de vitamina C tanto en niños como en mujeres reclama acciones programáticas para reducirlas.